Challenges in design and construction of deep excavation for KVMRT in Kuala Lumpur limestone formation - Tan, Y. C. (Penerbit UTM Press, 2016)
The Klang Valley Mass Rapid Transit (KVMRT) Sungai Buloh-Kajang Line project is the first Mass Rapid Transit (MRT) project in Malaysia. The KVMRT Project when completed will cover a distance of 51km and comprises of 31 passenger stations. This paper covers the challenges in design and construction of deep excavation works for three underground stations, namely Tun Razak Exchange (TRX) station, Cochrane Station and Maluri Station, as well as one portal (South Portal) all located in Kuala Lumpur limestone formation. The Kuala Lumpur Limestone formation exhibits notorious karstic features with irregular bedrock profiles, variable weathering condition, cavities and slime zones. This paper presents the design principles of temporary earth retaining system together with vertical rock excavation to the final depth of the station in karstic limestone formation. The unique experience (design and construction) gained from this project will be a useful reference for similar excavation works, especially in karstic limestone formation.